The Effect of Active, Creative, Effective, and Enjoyable Learning Models on the Fourth-Grade Students’ Learning Outcomes - Rika Olimina Malau; Patri Janson Silaban; Rebekah Kairani Sembiring; Bogor Lumbanraja; Rumiris Lumban Gaol (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the effect of using the PAKEM learning model on students’ learning outcomes on the theme of the area where I live in class IV of SD Negeri 097795 Perasmian in the academic year 2022/2023. The study uses quantitative methods. The research population is 132 students from the entire class I-VI of SD Negeri 097795 Perasmian. Sampling uses a purposive sample with a number of 30 students from class IV. The research results indicate that students’ learning outcomes using the PAKEM model are included in the very good category with an average score of 85.13 and a correlation test result of 0.841, which means rcount (0.841) ≥ rtable (0.361), hence Ha is accepted. Thus, there is a significant effect between the use of the PAKEM learning model and students’ learning outcomes on the theme of the area where I live in class IV of SD Negeri 097795 Perasmian. It can be seen from the research results of the T-test, where tcount 8,215 ≥ ttable 2,048, Ha is accepted. It reveals that there is a significant positive effect from the use of the PAKEM learning model on students’ learning outcomes in the theme of the area where I live in class IV of SD Country 097795 Perasmian in the academic year 2022/2023.